LINGUISTIC MEANS FOR DETERMINING CONDITIONAL RELATIONS IN MODERN SPANISH LANGUAGE AS LINGUISTIC BEHAVIOR OF COMMUNICANTS - Sudorzhenko, Galina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article focuses on the analysis of linguistic units of the Spanish language, which differ in syntactic structure and convey conditional attitudes depending on the communicative situation. The specifics of the use of these units in the communication process are determined. Given the thought-speech activity of the character, the structural patterns of conditional-consequential relations are described. The criteria for the allocation of conditional relations are revealed. The essence of the notion is defined as a condition and a communicative situation is defined, in which the speaker demonstrates his competence to express conditional attitudes, the realization of which is the opposite of reality, or to create a possible world for the realization of such a situation. The main types of sentences in Spanish are discussed, which reflect the condition-effect relationship, while also capable of transmitting other shades, thereby signaling the speech behavior of a person. The choice of illustrative material was confined to the authors who represented the literature of the end of the 20th – the beginning of the 21st century, which made it possible to reveal the essential characteristics of the mentality of contemporary native speakers, which determine the national specificity of the use of linguistic means in the communication process. The paradigmatic approach to the systematization of syntactical units identified an intricate sentence with a subordinate condition with the basic structure of conditional-consequential relationships. The relationship between the language and its user, the bearer of culture, traditions, and rules of conduct in society, made it possible to characterize their thinking and speech behavior by analyzing the use of language means. ___________ References • Montolío E., V. Barreto. Las construcciones condicionales. Gramática descriptiva de la lengua española. Entre la oración y el discurso. Morfología (Madrid: Espasa Calpe, 2000): 3644–3735. • Ckitishvili, N. V. «Uslovnye predlozhenija v sovremennom ispanskom jazyke.» Avtoref. diss. kand. filol. nauk, Moskva, 1974. • Garrido Vilchez G. B. Las "Gramáticas" de la Real Academia Española : teoría gramatical, sintaxis y subordinación (Salamanca, Tesis Universidad de Salamanca, 2008), 962. • Rodríguez Ramalle T.M. Manual de sintaxis del español (Madrid, Ed. Castalia, 2005), 610. • Gómez Torrego L. Gramática didáctica del español (Madrid, S. M., 2002), 543. • Barco GómezC. Elementos de Lógica (Manizales, Universidad de Caldas, Centro Editorial, 2004), 288. • Jakobson, Z. Izbrannye raboty (Moskva, Progress, 1985), 455. • Rey, J. Dile a Maríaque la quiero (Barcelona, PenguinRandom House Grupo Editorial. S. A. U. 2016). • Sampedro,J. L. La sonrisa estrusca (Madrid, Ed. Alpaguara, S. A., 1996), 347. 10. Gala, A. Charlas con Troyo (Madrid, Escasa Calpe, S. A., 1986), 327.